PRELIMINARY STUDY OF SEDIMENT AGES AND ACCUMULATION RATES IN JAKARTA BAY DERIVED FROM DEPTH PROFILES OF UNSUPPORTED 210Pb - Ali Arman Lubis; Barokah Aliyanta (Universitas Gadjah Mada, 2006)
Preliminary study of sediment ages and accumulation rates has been carried out in Jakarta Bay using unsupported 210Pb. 210Pb occurs naturally in sediments as one of the radioisotopes in the 238U decay series. The total 210Pb activity in sediments has two components, namely; supported and unsupported. The latter derives from dissociation of 210Pb from 226Ra through diffusion of the intermediate gaseous isotope 222Rn which diffuse into the atmosphere and decay to 210Pb. 210Pb falling directly into seawater and deposit on the bed of the marine with sediments. 210Pb has half-life of 22.26 years makes it well suited to dating and determining the accumulation rate of sediments laid down over the past 100 - 150 years. Two cores samples with diameter 7.5 cm were taken by scuba divers from Jakarta Bay and were analyzed of 210Pb using α-spectrometer equipped with PIPS detector. The sediment ages and range of sediment accumulation rates of core I and II are up to 169 years and (0.25 - 1.93) kg/m2y and up to 157 years and (0.15 - 2.68) kg/m2y, respectively.